The investigation of genetic and clinical features in Chinese patients with juvenile amyotrophic lateral sclerosis. Issue 3 (20th April 2017) - Liu, Z.‐J.; Lin, H.‐X.; Liu, G.‐L.; Tao, Q.‐Q.; Ni, W.; Xiao, B.‐G.; Wu, Z.‐Y.
Abstract : Juvenile amyotrophic lateral sclerosis (JALS) occurs at an age of onset below 25 years with a heterogeneous disease onset location, variable progression and survival time. To investigate whether an ALS gene profile could resolve any aspects of clinical symptom heterogeneity, we have used targeted sequencing technology in a cohort of 12 JALS patients of Chinese descent. We detected 5 likely pathogenic mutations, 2 in familial probands and 3 in sporadic patients. One was a known TARDBP mutation (p.G348V) and 4 were FUS frameshift mutations including a known p.Gln519Ilefs*9 mutation and 3 novel mutations, p.Gly515Valfs*14, p.Gly486Profs*30, and p.Arg498Alafs*32. Of the 4 FUS mutations, 2 were able to be confirmed as de novo mutations. The TARDBP mutation carrier showed a classic ALS phenotype. All patients with FUS mutations experienced limb weakness at an early age and developed bulbar symptoms during the disease course. FUS mutations have previously been associated with increased JALS disease progression, however, we found a large range 12 to 84 months in disease survival (mean 58.2 months). Our results justify future screening for variants in FUS as it remains the most frequent genetic determinant of early onset, JALS (found in 30% of our patients). Abstract :